Assessing the performance of in-cylinder fuel injection for motorsport applications using spray visualisation and 3D simulation - Guzel, Cem Ali (Cranfield University, 2024)
The development of the next generation Formula One (F1) power unit (PU) is constrained by stringent resource limitations set by the Federation International de l’Automobile (FIA). Fuel injector performance is crucial for facilitating reliable ultra-lean combustion and thus achieving greater break thermal efficiencies (BTEs) for a significant competitive edge. The main challenges in developing an in-cylinder fuel injection strategy for an F1 internal combustion engine (ICE) is firstly the narrow 4 𝑚? time window for injection, evaporation, and homogeneous mixing, and secondly the generation of liquid film on the combustion chamber surfaces. Both of which are significant for maximising the fuel conversion efficiency, and therefore delivering a competitive next generation F1 ICE. A multi-hole fuel injector was tested in a constant volume quiescent chamber (CVQC) by a third party at F1 ICE relevant test conditions and an array of tools were developed in this research to process the results. The Spray Metrics Tool, Spatial Density Analysis Tool, and Phase Doppler Particle Analysis (PDPA) experiment enabled an extensive assessment of the injector performance in relation to the success metrics of an F1 ICE injector. Success in characterising performance is the ability to have all the fuel in vapor form in sufficient time before combustion and to minimise liquid wall film generation from spray impingement. The results from the CVQC test were used to correlate the computational fluid dynamics (CFD) predictions in the search for an optimal trade-off between computational efficiency and degree of experimental correlation. Future injector designs and injection strategies could then be assessed in an ICE CFD simulation and a number of which result in the highest predicted BTEs would be produced.
Brighton, James L. - Associate Supervisor
Keywords: Spray Morphology; Droplet Breakup; ICE; Injector Performance; Imaging; PDPA; CFD